Clinical case of hemophagocytic lymphohistiocytosis: rare or undiagnosed syndrome? - O. B. Yaremenko; A. O. Sydorova; O. Ya. Antoniuk (Zaporožskij Medicinskij Žurnal)
Hemophagocytic lymphohistiocytosis (hemophagocytic syndrome, HLH) is a life-threatening hyperinflammatory condition associated with a high mortality rate; it is characterized by hyperstimulation of histiocytes and cytotoxic T-cells, which leads to cytokine storm and multisystemic injury.